The development of tools for network analysis in the honey bee (Apis mellifera L.) - Lecocq, Antoine (2011)
The honey bee (Apis mellifera) has accompanied Man for thousands of years, and yet somehow, some aspects of this most studied of insects remain uncertain. To this day, details of the physiology, disease transmission, social organisation and behaviour of this animal are still unclear. The development of technology and computing and the use of tagging and automatic monitoring have already contributed in shedding light on some of the intricacies of sociality amongst insects. In this project, we hoped to develop further tools for the study of disease transmission though social networks in the honeybee, and shed some light on factors which might affect the behaviour of the bees in an experimental setting. Bees were exposed to Kashmir Bee Virus and Nosema ceranae spores, and we attempted to identify the route of transmission of the diseases to sets of uninfected bees. Induced defecation was attempted by exposing honey bee workers to various treatments. Finally, bees were exposed to infra-red and white light treatments in an observation hive in order to determine whether artificial light had an impact on honey bee movement and locomotor activity. Whilst we would have expected the Kashmir Bee Virus to be transmitted through food exchange, we found no evidence of such pathway. Similarly, bees infected with Nosema ceranae spores did not seem to infect other workers through trophallaxis. Induced defecation in worker bees was generally unsuccessful and more work needs to be carried out to identify whether a reliable method can be discovered. Preliminary results of the impact of lights on the activity of the bees in an observation hive support the hypothesis that lights do affect bees for a short period. This body of work should serve as a development of the tools needed for advanced studies of the social networks and exchanges in honey bee colonies.